Efficacy and Renal Safety of Dapagliflozin in Patients with Type 2 Diabetes Mellitus Also Receiving Metformin: A Real-Life Experience. (3rd May 2018) - Scorsone, Alessandro; Saura, Gabriella; Fleres, Mattia; Spano, Lucia; Aiello, Vito; Brancato, Davide; Di Noto, Anna; Provenzano, Francesca; Provenzano, Vincenzo
Abstract : Introduction . This study aimed at evaluating the efficacy and safety of dapagliflozin in patients with type 2 diabetes (T2D) who also received metformin in clinical practice in Italy. Methods . This was a retrospective observational study and it included data from patients who received dapagliflozin 10 mg once daily in conjunction with metformin for 12 months (DAPA + MET). In those with inadequate glycemic control, insulin or glimepiride was added after 30 days (DAPA + MET + other glucose-lowering drugs). Efficacy assessments included glycosylated hemoglobin (HbA1c ) levels at 6 and 12 months, as well as body mass index (BMI) and lipid parameters at 12 months. Safety was also assessed. Results . Data on 66 patients were included. In both groups, HbA1c was significantly reduced at 6 and 12 months compared with baseline and significant reductions in HbA1c were observed at 12 months compared with 6 months. Over the 12-month treatment period, dapagliflozin significantly reduced BMI in both groups. No significant changes in lipid parameters were observed in either group and no detrimental effects on renal function were detected. Conclusions . Dapagliflozin is effective and safe in patients with T2D also receiving metformin. Glycemic control was already achieved with dapagliflozin + metformin, and add-on therapy was not associated with further improvements.